Change 2.0 Beyond Organisational Transformation - Klewes, Joachim; Langen, Ralf.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2008)
Joachim Klewes is Senior Partner of Pleon and an associate professor at the Heinrich Heine University Duesseldorf. His over 25 years of expertise include major assignments in the fields of organisational consulting, corporate change and crisis management, as well as corporate communications. He is a founding partner of the opinion research institute com.X and a frequent writer, publisher and speaker. Ralf Langen is Managing Partner of Pleon Germany and European Head of Pleon$1 (Bs Change & Transformation Practice. He has been a communications management professional for more than 15 years both on the industry side and as a consultant. He specialises in change management, and crisis and issues management. He is also the founder and chairman of the European Centre for Reputation Studies (ECRS). Pleon is Europe's leading communications consultancy, creating and implementing strategies for private and public sector organisations around the world. The agency has 33 branded offices with more than 1,000 employees in 16 European countries and associate agencies in ten countries across Europe, the Middle East and Africa. Pleon was recently named "European Consultancy of the Year" by the Holmes Report and "Best Public Relations Agency" in The 2008 International Business Awards. "Change before you have to" - the advice by Jack Welch, former CEO of industry giant General Electric, still holds true today. Even more so: organisations permanently have to face change, if they want to succeed economically. No small feat, given the high expectations that employees have in times of transformation towards their management. Staff cannot be entirely left out of the process, anymore. This hard-learned lesson is fairly well understood by now. But how should engagement be designed and carried out? This collection explores the different approaches to employee participation - from a practitoners' perspective. Consultants from Pleon, Europe's leading communications agency, as well as managers and academics share their experience with change communication and offer valuable insights on what engagement - if tackled correctly - can do for organisations: it adds to the internal trust and external reputation.s
Incite -- It may come as a surprise: Successful change management is mainly a matter of letting it happen -- The human factor in change processes: Success factors from a socio-psychological point of view -- Accelerated change dynamics within the healthcare industry: Just a trend, or is there more to it? -- The power of ideas $1 (BReputation management and successful change -- Change management in alliances -- Insight -- Winning people$1 (Bs hearts and minds -- Use of multipliers in change communication: How credible personal communication can make change effective -- Why engagement matters $1 (BFrom command and control to collective learning via social software -- The importance and use of analyses in change management -- Inside -- The quiet transformation of an ugly duckling: The German Federal Employment Agency$1 (Bs gradual transition $1 (BFrom a bottomless pit for taxpayers$1 (Bmoney to an efficient service provider -- How to develop a strategic business unit within a historical and sound structure: The formation of Radeberger Group -- Managing complex change: Challenges at the National Health Service Greater Glasgow and Clyde -- Taming the lion: How to keep a programme office up and running -- Beyond -- A matter of trust $1 (BA journey through the Five Continents of Change Management.s
Keywords: Business; Management science; Entrepreneurship; Management; Leadership; Personnel management; Business and Management; Business Strategy/Leadership.; Business and Management, general; Management; Entrepreneurship; Human Resource Management; Electronic books